2011
DOI: 10.4025/enfoque.v30i3.13117
|View full text |Cite
|
Sign up to set email alerts
|

Análise epistemológica da valoração como constructo para decisões estratégicas: óticas contábil e econômica

Abstract: RESUMODiversas abordagens teóricas nas áreas contábil e econômica procuram determinar a melhor forma de emprego do conceito "valor" na atividade empresarial. Neste trabalho, dimensionam-se algumas questões associadas à aplicação desse conceito na Contabilidade, já que o tema tem proporcionado interpretações e visões díspares por parte da academia e dos usuários. Este ensaio teórico traz à tona diferenças na atribuição de valor de custo entre a Contabilidade e a Economia. Para isso, analisam-se algumas das prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Views on the relevance of biological asset information were initially identified. It was verified that professionals who are in favor of the rule realize that the reported information are useful and important for the decision making, which brings a greater prediction values for the financial reporting, making the -ER, 2003;COSENZA;LAURENCEL, 2011;ELAD, 2004;ELAD;HERBOHN, 2006;WATTS, 2003).…”
Section: Accounting Professionals' Perception Of Fair Value Accountinmentioning
confidence: 90%
See 1 more Smart Citation
“…Views on the relevance of biological asset information were initially identified. It was verified that professionals who are in favor of the rule realize that the reported information are useful and important for the decision making, which brings a greater prediction values for the financial reporting, making the -ER, 2003;COSENZA;LAURENCEL, 2011;ELAD, 2004;ELAD;HERBOHN, 2006;WATTS, 2003).…”
Section: Accounting Professionals' Perception Of Fair Value Accountinmentioning
confidence: 90%
“…The superiority of fair value accounting on the historical cost is due to its capacity to incorporate new market conditions in the accounting numbers, providing more relevant useful information for economical decision making (ARGILÉS; GAR-CIA-BLANDON; MONLLAU, 2011; ARGILÉS BOSCH; ALIBERCH; BLANDÓN, 2012; ATHA-NASIOS; STERGIOS; LASKARIDOU, 2010; BARLEV; HADDAD, 2003; BARTH; LANDSMAN; LANG, 2008;DOWLING;GODFREY, 2001;GONÇALVES;LOPES;CRAIG, 2017;LEFTER;ROMAN, 2007;PENG;BEWLEY, 2010). However, there are several criticisms to fair value because it is an estimate-based measurement, mainly for assets that do not possess an active market and that consequently demand high level of judgement from the accounting professional (BOOTH; WALK-ER, 2003;COSENZA;LAURENCEL, 2011;ELAD, 2004;ELAD;HER-BOHN, 2006;WATTS, 2003). Argilés Bosch, Aliberch and Blandón (2012), Bohušová, Svoboda and Nerudová (2012), Rech and Pereira (2012), Hinke and Stárová (2013), Maina and Wingard (2013) and Mates et al (2015) identified the obstacles, difficulties and shortcomings as well as the benefits and advantages of IAS nº 41 implementation.…”
Section: Introductionmentioning
confidence: 99%